Mechanically and electromagnetically tuned lattice structures via additive manufacturing: a dual-functional design approach using PLA - Mahouti, Tarlan; Belen, Mehmet Ali; Yilmazer, Hakan (IOP Publishing Ltd, 2026)
Lattice structures are promising for lightweight biomedical implants due to high strength to weight ratios and porous architectures that mimic bone. In this study, the effects of pore size, porosity, wall thickness, and unit cell geometry on the mechanical and electromagnetic (EM) performance of polylactic acid lattice scaffolds fabricated via fused deposition modeling are systematically investigated. Using a Taguchi L9 design, nine lattice variants were fabricated: hexahedron (H-series), gyroid (G-series), rhombicuboctahedron (R-series) geometries with pore sizes of 200-600 & micro;m and wall thickness of 300-500 & micro;m. Compression tests and finite element analysis were performed to identify optimal designs. The hexahedron geometry achieved the highest fidelity to the computer aided design and superior compressive strength, with sample H36 (500 & micro;m pore, 300 & micro;m wall) exhibiting an elastic modulus of similar to 530 MPa and yield strength similar to 14 MPa, closest to the range of trabecular bone. Only the most porous gyroid and rhombic samples fell below the 100 MPa elastic modulus threshold for bone applications. Building on these results, the optimized H36 lattice was repurposed as a dielectric substrate for a microstrip antenna. Both simulation and experiment confirmed a resonance at 6.6 GHz with a minimum S-1(1) of -17.4 dB and a broad similar to 3.2 dBi gain pattern, demonstrating effective EM operation without loss of mechanical integrity. This dual functionality combining structural support and wireless capability introduces a new direction for smart lattice implants and sensor integrated lightweight components.
Keywords: lattice structures; additive manufacturing; mechanical properties; electromagnetic performance; antenna integration; SCAFFOLDS; FABRICATION; Instruments & Instrumentation; Materials Science